2016
DOI: 10.5219/563
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of protein fractions and antioxidant activity of Chia seeds (Salvia hispanica L.)

Abstract: Chia seed (Salvia hispanica L.) is an annual herbaceous plant categorized under Lamiaceae family. Chia seeds were investigated as a source of proteins and natural antioxidants. It is a potential alternative source of high quality protein, fats, carbohydrates, high dietary fibre, vitamins and mineral elements. The objective of this study was to evaluate chia seed from protein content and antioxidant acivity and highlight the quality of this pseudocereal. A crude protein, moisture content, content of protein fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…The storage proteins are those proteins which are present to supply intermediary nitrogen compounds for biosynthesis at a metabolically active stage of seed development (López et al, 2018). The main storage proteins present in chia are prolamins, glutelins, albumins, and globulins, the latter two are found in greater quantity than the others (Kačmárová, Lavová, Socha, & Urminská, 2016;Orona-Tamayo et al, 2015;Sandoval-Oliveros & Paredes-López, 2013). The amount of protein may vary according to the botanical source, plant variety, preparation of the meal, extraction method, and other factors (Vázquez-Ovando et al, 2010).…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…The storage proteins are those proteins which are present to supply intermediary nitrogen compounds for biosynthesis at a metabolically active stage of seed development (López et al, 2018). The main storage proteins present in chia are prolamins, glutelins, albumins, and globulins, the latter two are found in greater quantity than the others (Kačmárová, Lavová, Socha, & Urminská, 2016;Orona-Tamayo et al, 2015;Sandoval-Oliveros & Paredes-López, 2013). The amount of protein may vary according to the botanical source, plant variety, preparation of the meal, extraction method, and other factors (Vázquez-Ovando et al, 2010).…”
Section: Nutritional Qualitymentioning
confidence: 99%
“…More intense bands were observed in the range of 50–60 kDa, attributed to the presence of 11 S globulin. Under non-reducing conditions, the 11 S globulin can be resolved into monomers with MW from 50 to 60 kDa ( Sandoval-Oliveros and Paredes-López, 2013 ; Kačmárová et al, 2016 ). It has been confirmed that 11 S globulin is the most abundant protein in chia seeds ( López et al, 2018a ; Wang et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies demonstrated that Salvia extracts had significant antioxidant activity by different methods among which DPPH, FRAP, TEAC, and ABTS (Asadi et al, 2010;Kačmárová et al, 2016).…”
Section: Resultsmentioning
confidence: 99%